Stochastic Ageing and Dependence for Reliability - Lai, Chin Diew.; Xie, Min.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2006)
Ageing and dependence are two important characteristics in reliability and survival analysis, and they affect significantly the decision people make with regard to maintenance, repair/replacement, price setting, warranties, medical studies, and other areas. There are many papers published at different technical levels. This book aims at providing a state–of-the-art review of the subject so the interested readers may have a panoramic view of the theory and applications of the two areas. This book serves as reference book for professors and researchers involved in reliability and survival analysis. Students with basic probability and statistics knowledge interested in applications will also find the book useful. C.D. Lai obtained Ph.D. in Statistics from the Victoria University of Wellington. He held positions at the University of Auckland and the National Chiao Tung University (Taiwan) prior to coming to Massey in 1979. Professor Lai has published over 90 peer–reviewed papers and coauthored two well-received books. He is one of the two Editors-in-Chief of the Journal of Applied Mathematics and Decision Sciences. M. Xie obtained his Ph.D. in Quality Technology from Linkoping University in Sweden. He joined the National University of Singapore in 1991 and was awarded the prestigious Lee Kuan Yew research fellowship. Professor Xie has authored numerous papers and several books, and serves as editor or editorial board member in several international journals.
Concepts and Applications of Stochastic Ageing -- Bathtub Shaped Failure Rate Life Distributions -- Mean Residual Life — Concepts and Applications in Reliability Analysis -- Weibull Related Distributions -- An Introduction to Discrete Failure Time Models -- Tests of Stochastic Ageing -- Bivariate and Multivariate Ageing -- Concepts and Measures of Dependence in Reliability -- Reliability of Systems with Dependent Components -- Failure Time Data.
Keywords: Statistics .; Computer software—Reusability.; Operations research; Decision making; Quality control; Reliability; Industrial safety; Probabilities; Statistics for Engineering, Physics, Computer Science, Chemistry and Earth Sciences; Statistics for Business, Management, Economics, Finance, Insurance; Performance and Reliability; Operations Research/Decision Theory; Quality Control, Reliability, Safety and Risk; Probability Theory and Stochastic Processes